2018
DOI: 10.1634/theoncologist.2017-0597
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in Pretreated Mantle Cell Lymphoma Patients: An Italian Observational Multicenter Retrospective Study in Daily Clinical Practice (the Lenamant Study)

Abstract: Several factors influence treatment choice in relapsed/refractory mantle cell lymphoma (rrMCL), and the therapeutic scenario is continuously evolving. In fact, rrMCL became the first lymphoma for which four novel agents have been approved: temsirolimus, lenalidomide, ibrutinib, and bortezomib. The rrMCL therapeutic algorithm is not so well established because data in the everyday clinical practice are still poor. Lenalidomide for rrMCL patients is effective and tolerable even in a real-life context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This is a common issue which may presumably be solved at least partially with combination or right sequencing therapy [ 13 , 14 ]. Lenalidomide could be an effective opportunity even if in our study the patients (only five) who underwent lenalidomide after ibrutinib failed to achieve response [ 15 , 16 ]. On the other hand, patients who consolidated response with SCT had better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is a common issue which may presumably be solved at least partially with combination or right sequencing therapy [ 13 , 14 ]. Lenalidomide could be an effective opportunity even if in our study the patients (only five) who underwent lenalidomide after ibrutinib failed to achieve response [ 15 , 16 ]. On the other hand, patients who consolidated response with SCT had better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple phase II studies have been conducted with lenalidomide alone and in combination with rituximab (R 2 regimen) [35][36][37][38][39][40][41][42]64]. The pivotal phase II MCL-001 (EMERGE) study in the US established the activity of lenalidomide in relapsed/refractory MCL, including patients who received prior bortezomib (median 4 prior regimens) [35].…”
Section: Novel Monotherapy Treatment Options For Relapsed/refractory MCLmentioning
confidence: 99%
“…In this regard, 22.8% and 45.7% of the patients were refractory to the first and the most recent line of therapy, respectively ( Table 1 ). The authors reported a median PFS of 13.8 months, a median OS of 32.5 months, an ORR of 47.1%, and a CR of 31.4% 31 ( Table 4 ). Similarly, the study of Zinzani et al, which included 33 patients with R/R MCL treated with lenalidomide, reported a PFS of 13.9 months, an ORR of 45.5% and a lower CR of 12.1% 32 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%